(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article delves into the world of charming poetry created by Muhammad Yusuf and focuses on his skillful use of phrases. The article explores the importance of these phrases, their thematic significance and their impact on readers. Through careful analysis, we emphasize how Joseph’s poetry transcends language and emotion, leaving an indelible mark on the literary landscape.